2021
DOI: 10.3390/jcm10214944
|View full text |Cite
|
Sign up to set email alerts
|

How Should Patients with a Thoracolumbar Injury Classification and Severity Score of 4 Be Treated?

Abstract: The thoracolumbar injury classification and severity score (TLICS) system help surgeons decide whether patients should undergo initial operative treatment or nonoperative treatment. However, the best treatment for patients with TLICS 4 fracture remains unknown. The aim of this study was to identify the risk factors for nonoperative treatment failure in patients with TLICS 4 fracture and establish treatment standards for TLICS 4 fractures. This study included 44 patients with TLICS 4 fracture who initially rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…To determine whether this difference is clinically significant, a predetermined MCID of 3.8° was used. Since there is no widely accepted MCID for this variable, an anchor-based method was employed, as described in a 2021 article by Lee et al, 9 which reported that a difference of 3.8° or higher correlated with clinical outcomes. Upon applying this MCID to our analysis, the confidence intervals of the pooled effect estimate of kyphotic angulation were found to include 3.8°, raising doubts about its clinical significance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To determine whether this difference is clinically significant, a predetermined MCID of 3.8° was used. Since there is no widely accepted MCID for this variable, an anchor-based method was employed, as described in a 2021 article by Lee et al, 9 which reported that a difference of 3.8° or higher correlated with clinical outcomes. Upon applying this MCID to our analysis, the confidence intervals of the pooled effect estimate of kyphotic angulation were found to include 3.8°, raising doubts about its clinical significance.…”
Section: Discussionmentioning
confidence: 99%
“…The minimal clinically important difference (MCID) of pain VAS, ODI, RMDQ, and kyphotic angulation were defined as 11, 7 7.8, 7 5, 8 and 3.8°, respectively. 9 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation